Losing reality : on cults, cultism, and the mindset of political and religious zealotry - Lifton, Robert Jay, 1926- (New York : The New Press, 2019)
"A definitive account of the psychology of zealotry, from a National Book Award winner and a leading authority on the nature of cults, political absolutism, and mind control"--
Chinese communist thought reform -- Revolutionary immortality -- Ideological totalism -- the "eight deadly sins" -- On cultism and the larger society -- Aum Shinrikyō -- Nazi doctors -- Trump -- The apocalyptic twins: nuclear and climate threats -- The protean alternative -- Regaining reality.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on February 05, 2020).
eBooks on EBSCOhost
Keywords: Fanaticism; Brainwashing; Cults; Religion and politics; Fanatisme; Lavage de cerveau; Religion et politique; MEDICAL -- Neuroscience; Brainwashing; Cults; Fanaticism; Religion and politics; SOCIAL SCIENCE / Sociology / Social Theory